The Ottoman Dynasty Economic Policy and Its Relevance in the Midst of Global Economic Dynamics in 2025 - Fauzan Romadhian Khairi; Euis Amalia; Desmadi Saharuddin (Universitas Darunnajah, 2025)
Most studies of the economic policies of the Ottoman Dynasty are historical in nature and have not been much associated with contemporary global economic dynamics. In fact, Ottoman economic principles such as the open market system, fiscal flexibility, and waqf management for social welfare have potential relevance in the face of current global economic challenges, including inequality, market instability, and the need for a sustainable economic model. This research aims to: identify the main principles of Ottoman economic policy; analyze its relevance to the global economic challenges of 2025; and formulating historical-based economic policy recommendations that are adaptive to the modern context. A qualitative approach with historical comparative analysis methods is used to compare primary data from the Ottoman archives (trade records, fiscal policy) with contemporary data for comparison and relevance points to economic policies in the present. The results of the study show that the principles of Ottoman economics have significant relevance, particularly in encouraging inclusive and sustainable economic models. The waqf system can be adapted as a stable social funding mechanism, while fiscal flexibility provides inspiration for adaptive economic policy responses amid global uncertainty. This research contributes to the development of historical economic discourse in modern contexts and offers a hybrid policy model that integrates traditional values with contemporary economic needs.